Hedonic ratings and consumption of breakfast - Nurhazwani Abdullah; Siti Syazwani Abdullah; Rozita Jamaluddin; Hazrina Ghazali (2014)

(untitled)
This research is to examine the relationship between hedonic ratings and the consumption of breakfast food during basic recruit training. Hedonic ratings of breakfast items belonging to 30 food items provided by the catering were collected from 50 recruits, over 2 months. All foods and drinks provided by the catering were rated from 1 (extremely disliked) to 9 (extremely liked), with a score of 5 set as acceptable score. During the subsequent breakfast, the leftovers of each individual and menu item were recorded. Hedonic responses to breakfast food items differed significantly [F (29) = 103.62, p<0.05]. 53.3% of breakfast food items were scored from 5.12 to 8.52. Honeystar cereals (score 8.52) and nasi lemak (score 8.10) were liked very much with more than 90% of consumption. The least liked breakfast food was kway teow soup with score of 1.58. A significant and high correlation was found between hedonic scores and food consumption of breakfast food items (r= 0.725) (p<0.05). In conclusion, hedonic ratings of recruits predicted the amount of breakfast consumption. Low ratings of breakfast food items raise the question on how the breakfast food should be served to encourage their consumption in recruits during training.